Antioxidant vitamins in asthma - Columba Citlalli Barrera-Mendoza; Francisco Ayala-Mata; Christian Cortés-Rojo; Martha Estrella García-Pérez; Alain Raimundo Rodríguez-Orozco (Revista Alergia México, 2018)
Asthma is a condition of unknown etiology characterized by chronic airway inflammation. Cells that mediate the inflammatory response generate reactive oxygen species that, together with other respiratory tract naturally-occurring oxidant species, produce a rupture of the redox balance, generating oxidative stress. It has been proposed that oxidative stress can be reverted by supplemental or dietary intake of antioxidant vitamins such as vitamin A, C, D and E, and this way relieve, improve or protect people with asthma. In this research, observational and placebo-controlled trials with regard to the role of antioxidant vitamins in the course of asthma, published between 1979 and 2016, were reviewed. The search engines were Google and Google Scholar, whereas consulted databases were PubMed and The Cochrane Library. There were 75 articles relevant to the subject that were found and reviewed, and it was concluded that it is not clear if the intake of supplements of these vitamins has any beneficial clinical effect on asthma control. Further controlled, longer trials are needed to elucidate the role of these nutrients in the course of asthma.